The Empowerment For Women's Economic With Productive Financing at Bank BTPN Syariah - Trimulato; Andi Zulfikar Darussalam; Syarifuddin; Sri Wahyuni (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2021)
The aim of this study is to find out the financing patterns provided by bank BTPN Syariah to special customers of pre-poor women in improving their micro-businesses. And to find out the increase in the growth of financing channeled by bank BTPN Syariah. The type of research in this paper uses literature research, taking data that has been presented from available sources. Then the author processes from the existing data sources. Sources of research data in research that are relevant to the theme and formulation of the problem presented. This research is qualitative descriptive. The results of this study indicate that the development of financing at bank BTPN syariah experienced growth in the period June 2017 to June 2018 which grew by 18.128 percent. Bank BTPN syariah provides special microfinance for underprivileged women who have a business, this financing program is called the Future Package (PMD). The financing special for women, customers are not charged with collateral, customers always receive entrepreneurial guidance on a regular basis, customers have the opportunity to save at Bank BTPN Syariah, and customers can take advantage of mobile phone technolgy facilities with Wow IB bank BTPN Syariah program. The results of this study indicate that the bank BTPN Syariah has carried out a financing program specifically provided for pre-prosperous women, in a plan to fix their family's economy. Pre-prosperous women's special financing at Bank BTPN Syariah has been enjoyed by its customers. With Islamic financing, customers can obtain business capital from one million to four million to develop their business. Pre-prosperous women's special financing is a financing product that is only owned by Bank BTPN Syariah. Even financing products at Bank BTPN are devoted to PMD productive financing and do not serve consumptive financing. So the funds of depositors can be channeled directly to productive economic activities.